Changes of brain structure and structural covariance networks in Parkinson’s disease associated cognitive impairment - Liu, Rong-Pei; Lin, Guo-Liang; Ma, Lu-Lu; Huang, Shi-Shi; Yuan, Cheng-Xiang; Zhu, Shi-Guo; Sheng, Mei-Ling; Zou, Ming; Zhu, Jian-Hong; Zhang, Xiong; Wang, Jian-Yong (Frontiers in Aging Neuroscience, 2024)
Background Cognitive impairment (CI) is common in Parkinson’s disease (PD). Multiple brain regions and their interactions are involved in PD associated CI. Magnetic resonance imaging (MRI) technology is a non-invasive method in investigating brain structure and inter-regional connections. In this study, by comparing cortical thickness, subcortical volume, and brain network topology properties in PD patients with and without CI, we aimed to understand the changes of brain structure and structural covariance network properties in PD associated CI. Methods A total of 18 PD patients with CI and 33 PD patients without CI were recruited. Movement Disorder Society Unified Parkinson’s Disease Rating Scale, Hoehn and Yahr stage, Mini Mental State Examination Scale, Non-motor Symptom Rating Scale, Hamilton Anxiety Scale, and Hamilton Depression Scale were assessed. All participants underwent structural 3T MRI. Cortical thickness, subcortical volume, global and nodal network topology properties were measured. Results Compared with PD patients without CI, the volumes of white matter, thalamus and hippocampus were lower in PD patients with CI. And decreased whole-brain local efficiency is associated with CI in PD patients. While the cortical thickness and nodal network topology properties were comparable between PD patients with and without CI. Conclusion Our findings support the alterations of brain structure and disruption of structural covariance network are involved in PD associated CI, providing a new insight into the association between graph properties and PD associated CI.